History of Islamic Education in Indonesia and its Relevance to the Modern Era - Nurdiyanto, Nurdiyanto; Bahar, Faiz Arfan; Kurahman, Opik Taupik; Suhartini, Andewi (Edunesia : Jurnal Ilmiah Pendidikan, 2024)
Education in Indonesia generally has historical contributions from the pre-independence and post-independence periods. This research aims to analyze and describe the early history of the arrival of Islamic education in Indonesia. Moreover, this research uses a qualitative approach to determine its relevance to the modern era. They are using the library research method. The data sources in this research are two sources, namely primary and secondary. Primary: journal articles, E-Books, and other internet media. Secondary: online proceedings, magazines, newspapers, and other sources. The data collection technique is collecting from the sources that have been mentioned, then classifying them and then concluding. Meanwhile, the analysis technique used is descriptive analysis, namely by integrating general knowledge into specifics (inductive) based on the results of literature findings, which have been carried out in stages of collecting primary and secondary data, classifying them, and then drawing conclusions. The results of this research found that Islamic education in Indonesia started with the entry and development of Islam in Indonesia, early Islamic educational institutions in Indonesia, the role of walisongo in developing Islamic education in Java, education during the Dutch colonial period, Dutch policy in Islamic education, the existence of Islamic boarding school education. During the Dutch colonial era, and education during the Japanese colonial era. In conclusion, the arrival process of Islam in Indonesia has several historical views based on existing opinions and theories.